Carimontir marketing PLAN s(motor vehicle service application) - Fransisca Indra Triana Puspitasari; Edi Hamdi (Institute of Computer Science (IOCS), 2023)
The high number of motorized vehicle population in Indonesia makes the potential need for motor vehicle services high. The high number of motorized vehicle users reflects the very dense activity of the community, increasing the need for facilities that can simplify and cut time for servicing motorized vehicles that are supported by existing information systems. The potential need for motorcycle service and the development of information systems is the background for Carimontir to create technology based on motor vehicle service applications. With this application, it can make it easier for motorized vehicle owners to carry out vehicle services more quickly and practically anytime and anywhere, while for partners, it will be easier to reach potential consumers. In Carimontir'themarketing plan ofCarimechanirbegins with determining the segmenting and targeting of potential partners and customers by determining the company's positioning. Carimechanir's marketing mix uses the 4P method, namely Product, Price, Promotion, and Place. The company also prepares sales marketing and sales marketing budgets, then determines revenue stream scenarios and assumptions including preparing revenue stream projections.